Hubungan Kondisi Lingkungan Fisik Rumah dan Kebiasaan Orang Tua dengan Kejadian Pneumonia pada Balita di Puskesmas Waru Kabupaten Sidoarjo - Fuadi, Muhammad Yusron; Thohari, Imam; Narwati, Narwati; Rusmiati, Rusmiati (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
The spread of pneumonia cases among under-fives in East Java Province dominates the main rank in Indonesia with the incidence rate increasing every year. In 2020-2022, there were 685, 764, 774 cases of pneumonia in toddlers in the Waru Health Center working area. The purpose of this study was to determine the relationship between the condition of the physical environment of the house and parental habits with the incidence of pneumonia in toddlers in the Waru Health Center working area in 2024. This type of analytic observational study used a case-control design. The results of the Chi-Square statistical test obtained (p-value<0.05) mean that the physical environment of the house and parental habits are associated with the incidence of pneumonia in toddlers, namely ventilation (p-value=0.001), temperature (p-value=0.020), lighting (p-value=0.012), humidity (p-value=0.003), occupancy density (p-value=0.022), the habit of opening windows (p-value=0.003) and smoking habits (p-value=0.0036). Researchers suggest that the community pay more attention to the condition of the home environment and support healthy behavior by getting used to opening windows in the morning, not smoking and maintaining a clean house.